Fenomena self harm pada kalangan remaja dan faktor penyebabnya - As saidah, Filda Fuady (Maliki Interdisciplinary Journal, 2024)
During adolescence, an individual experiences cognitive, psychosocial and emotional development. During adolescence, there are many problems experienced and people are susceptible to negative actions, one of which is self-harm. The aim of this research is to determine the phenomenon of self-harm behavior in adolescents and the factors causing it. The method used in this research is the Library Search method which is described descriptively.